From instrumental utility to the rights of the ecosystem: the ecocentric turn in the face of the planetary crisis - Marchena Ramírez, Juan José (2026)
This article examines the conceptual shift from an instrumental conception of nature toward an ecocentric paradigm that recognizes its intrinsic value and, consequently, its own legal personhood. First, it analyzes the scientific diagnosis of planetary boundaries proposed by Steffen et al. (2015) and updated by Richardson et al. (2023), in order to subsequently support the ethical and legal need for a paradigm change. Likewise, it examines the constitutional and jurisprudential milestones in Latin America, particularly the cases of Ecuador, Bolivia, and Colombia, with the purpose of illustrating the construction of the non-human subject of rights. Finally, it discusses the challenges of the practical implementation of such a regime, such as the figure of guardians and their articulation with traditional administrative law.